Targeted metabolomics identifies the cytochrome P450 monooxygenase eicosanoid pathway as a novel therapeutic target of colon tumorigenesis - Wang, Weicang (Cancer Res, 2019)
Colon cancer is the third most common cancer and the second leading cause of cancer-related death in the United States, emphasizing the need for discovery of new cellular targets. Using a metabolomics approach, we report here that epoxygenated fatty acids (EpFA), which are eicosanoid metabolites produced by cytochrome P450 (CYP) monooxygenases, were increased in both the plasma and colon of azoxymethane (AOM)/dextran sodium sulfate (DSS)-induced colon cancer mice. CYP monooxygenases were overexpressed in colon tumor tissues and colon cancer cells. Pharmacological inhibition or genetic ablation of CYP monooxygenases suppressed AOM/DSS-induced colon tumorigenesis in vivo. In addition, treatment with 12,13- epoxyoctadecenoic acid (EpOME), which is a metabolite of CYP monooxygenase produced from linoleic acid, increased cytokine production and JNK phosphorylation in vitro and exacerbated AOM/DSS-induced colon tumorigenesis in vivo. Together these results demonstrate that the previously unappreciated CYP monooxygenase pathway is upregulated in colon cancer, contributes to its pathogenesis, and could be therapeutically explored for preventing or treating colon cancer.